SISTEM PENYIRAMAN OTOMATIS MENGGUNAKAN RTC (REAL TIME CLOCK) BERBASIS MIKROKONTROLER ARDUINO MEGA 2560 PADA TANAMAN MANGGA HARUM MANIS BULELENG BALI - Pratolo Rahardjo (Jurnal SPEKTRUM, 2021)
Along with technological developments, various technological innovations have begunto emerge that can be applied to facilitate individual or group work. One of them is the use ofappropriate technology, namely the use of technology in a field that can provide real benefit.Researchers designed an automatic watering system using RTC (Real time clock) based on theArduino Mega 2560 microcontroller. This watering system works automatically based on aspecified watering schedule according to the user's wishes. Users can set the watering timeeasily because the system is equipped with a keypad. Based on the results of tests carried out,the watering process occurs, when the time displayed on the LCD is the same as the timesetting given. Long watering duration of approximately 1 minute.